Number of Electroconvulsive Therapy Sessions required for Thai Psychiatric Patients: a Retrospective Study - Ittasakul P (Dove Medical Press, 2020)
Pichai Ittasakul,1 Siraprapha Vora-arporn,1 Punjaporn Waleeprakhon,1 Phern-Chern Tor2 1Department of Psychiatry, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Department of Mood and Anxiety, Institute of Mental Health, SingaporeCorrespondence: Pichai Ittasakul 270 Rama VI Road, Ratchathewi, Bangkok 10400, ThailandTel +662-2011478Fax +662-200-3277Email pichai.itt@mahidol.eduObjective: To study predictors of the number of electroconvulsive therapy (ECT) sessions required for symptom remission in psychiatric patients.Patients and Methods: We conducted chart reviews for 95 patients whose condition remitted following inpatient ECT. We analyzed the clinical characteristics of the patients and compared the number of ECT sessions between adult (age 18– 59 years) and elderly (age ≥ 60 years) patients.Results: The overall mean ± SD of the number of ECT sessions was 11.8 ± 4.7 (range: 6– 24). By diagnosis, it was 13.3 ± 5.5 for individuals with schizophrenia, 10.1 ± 2.7 for schizoaffective disorder, 14.4 ± 5.6 for bipolar depression, 9.4 ± 1.9 for bipolar mania, 10.9 ± 4.3 for major depressive disorder (MDD), and 11.8 ± 4.3 for those with other diagnoses. For MDD, the number of ECT sessions in elderly patients (13.4 ± 4.6) was statistically greater than that in adult patients (9 ± 2.9) (p = 0.008).Conclusion: The number of ECT sessions varied by age and diagnosis. The number of ECT sessions in elderly MDD patients was higher than that in adult MDD patients.Keywords: ECT, treatment, Thai patients, major depressive disorder, elderly